A3_2 If a Tree Falls... - Flood, Laura; Holland, Katie; Leversha, Thomas; Manley, Max (Physics Special Topics, 2022)
In this paper we are investigating the distances a person can be away from a tree to still be able to hear it fall. We have calculated that the furthest away a listener can be, with no noise from the surrounding area, to still be able to hear a tree fall is approximately 1000km and the furthest distance they can stand and still hear the noise in a city with traffic is 100m.